Risk assessment of pulmonary infections in primary glomerular diseases treated with rituximab - Yang, Chunyun; Li, Qiuyue (Frontiers in Immunology, 2025)
PurposeThis study aimed to evaluate the incidence and risk factors of pulmonary infections in patients with primary glomerular diseases (PGDs) treated with rituximab (RTX).MethodsClinical data of patients treated with RTX were collected, along with instances of pulmonary infections occurring within 6 months of RTX administration, to analyze risk factors associated with pulmonary infections in PGDs.ResultsA total of 246 patients were included in the study, comprising 169 with idiopathic membranous nephropathy (IMN), 53 with minimal change disease (MCD), nine with focal segmental glomerulosclerosis (FSGS), and 15 with IgA nephropathy (IgAN). Within 6 months, 39 patients developed pulmonary infections, corresponding to an infection rate of 15.85%. The infected group had higher age, serum creatinine (Scr), white blood cells (WBC), neutrophils (NEUT), neutrophil percentage-to-albumin ratio (NPAR), and proportion of latent tuberculosis than the non-infected group (p < 0.05). Conversely, serum albumin (sALB), estimated glomerular filtration rate (eGFR), complement component 3 (C3), and hemoglobin (HGB) were lower in the infected group (p < 0.05). No significant differences were observed between the two groups concerning gender, body mass index (BMI), comorbidities (hypertension, diabetes, and hepatitis B), concomitant use of corticosteroids or immunosuppressants, total dose of RTX, blood pressure, lymphocytes (LYM), percentage of neutrophils (NEUT%), urine protein-to-creatinine ratio (UPCR), C-reactive protein (CRP), serum immunoglobulin G (sIgG), and B-cell counts (p > 0.05). Four feature variables were identified through Least absolute shrinkage and selection operator (LASSO) binary logistic regression: sALB, age, C3, and eGFR. Univariate Cox proportional hazards regression analysis included clinically relevant factors and those differing significantly between groups (p < 0.1), identifying latent tuberculosis (LTB), age, C3, and eGFR as potential risk factors for infection (p < 0.05). sALB was identified as a potential protective factor (p < 0.01). Multivariate Cox proportional hazards regression analysis indicated that sALB is an independent protective factor against infection (p < 0.05); age, C3, and eGFR are independent risk factors (p < 0.01). The restricted cubic splines (RCS) curves showed that the risk of infection increased with advancing age and higher sALB but decreased with eGFR and C3. Furthermore, a non-linear association was observed between RTX dose and infection risk.ConclusionThe incidence of pulmonary infections within 6 months of RTX treatment in patients with PGDs was 15.85%. sALB is a protective factor against pulmonary infections, while age, C3, and eGFR are risk factors. The total dose of RTX, concomitant use of corticosteroids or immunosuppressants, and levels of sIgG, LYM, NEUT, and NPAR were not related to infection risk.